Phát triển hệ thống điện năng lượng mặt trời áp mái tại Việt Nam: Góc nhìn từ hành vi khách hàng - Nguyễn Hoàng, Việt; Vũ Tuấn, Dương; Nguyễn Thị Mỹ, Nguyệt; Ngô Thế, Sơn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Leading consumer behaviour toward renewable energy consumption is considered a strategic solution that ensures national energy security as well as attaining sustainable development goals. This study aims to evaluate the impact of several factors on the intention to use rooftop solar power in the Vietnamese market. On the basis of expanding the Theory of Planned Behaviour (TPB) and a SEM analysis for a sample of 515 consumers, governmental supportive policies, subjective norms, attitude were proven to significantly encourage the consumers’ planned behaviour. In contrast, the monetary barrier was confirmed to be a hindrance. In particular, the impact of brand trust was not clearly displayed. Finally, environmental knowledge was identified to be negatively correlated with the perceived monetary barrier. On top of adding to the knowledge of renewable energy consumption behaviour in emerging economies, the findings also suggest helpful implications to enterprises and policy-makers in the specific field of solar rooftop panels per their development of this market and establishing the renewable energy system in Vietnam.